Em razão de sua raça: os impactos psicossociais das desqualificações das masculinidades negras - Oliveira, Daniel Amâncio de (2024)
The construction of Brazil intertwined with racism is marked by the exploitation and subjugation of black bodies, equating them to commodities, devoid of humanity. The black male figure, as history demonstrates, has faced numerous attempts of annihilation, both literal and symbolic, whether in the post-abolition whitening policies, in the ongoing mass incarceration where prisons are predominantly occupied by black men with low education levels, in psychiatric institutions (psychiatric hospitals and therapeutic communities), in police violence rates, or in the construction of harmful stereotypes that evoke fear and prejudice in social relations. This research sought to present and contribute to the dialogue about masculinities and mental health among the black population, focusing on the psychosocial impacts in the construction of black masculinity in Brazilian society and worldwide, due to the systematic process of disqualifying their existences. The main objective of this dissertation was to investigate the consequences of racism on health processes and the possible psychological suffering of black men, based on interviews with four of them. Through the episodic analysis chosen with Kilomba (2019), it was possible to identify the following psychosocial impacts: difficulty in constructing a positive self-identity, internalization of negative stereotypes about black men, such as the need to perform high sexual performance, virile masculinity, self-pressure to be the best, not having the right to make mistakes, feelings of neglect and rejection. Additionally, we also found impaired social relations and concrete disadvantages due to social readings derived from colonial fantasies that depict them as dangerous and hypersexualized, corresponding to a process of objectification and inferiorization. Beyond our initial hypothesis, it was also possible to identify various forms of coping and constructing positive identities capable of subverting negative stereotypes and some oppressions, as well as discovering support networks that strengthen this resistance, such as family of origin, religion, romantic relationships, mental health care, and "aquilombamento". Thus, possible pathways are pointed out for an approach and adequate support in the mental health care of black men from an anti-racist, anti-colonial, anti-asylum, and anti-medicalization perspective.